T3/TRs axis in hepatocellular carcinoma: new concepts for an old pair. Issue 8 (August 2016) - Perra, Andrea; Plateroti, Michelina; Columbano, Amedeo
Abstract : Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide, and its burden is expected to further increase in the next years. Chronic inflammation, induced by multiple viruses or metabolic alterations, and epigenetic and genetic modifications, cooperate in cancer development via a combination of common and distinct aetiology-specific pathways. In spite of the advances of classical therapies, the prognosis of this neoplasm has not considerably improved over the past few years. The advent of targeted therapies and the approval of the systemic treatment of advanced HCC with the kinase inhibitor sorafenib have provided some hope for the future. However, the benefits obtained from this treatment are still disappointing, as it extends the median life expectancy of patients by only few months. It is thus mandatory to find alternative effective treatments. Although the role played by thyroid hormones (THs) and their nuclear receptors (TRs) in human cancer is still unclear, mounting evidence indicates that they behave as oncosuppressors in HCC. However, the molecular mechanisms by which they exert this effect and the consequence of their activation following ligand binding on HCC progression remain elusive. In this review, we re-evaluate the existing evidence of the role of TH/TRs in HCC development; we will also discuss how TR alterations could affect fundamental biological processes, such as hepatocyte proliferation and differentiation, and consequently HCC progression. Finally, we will discuss if and how TRs can be foreseen as therapeutic targets in HCC and whether selective TR modulation by TH analogues may hold promise for HCC treatment.